Fisheries technology management at Indian Council of Agricultural Research (ICAR): An IPR perspective - SINGH, VIKRAM; CHAKRABORTY, KAJAL (The Indian Journal of Animal Sciences, 2015)
Technology management in intellectual property rights (IPR) is a procedure, which incorporates technology production, promotion and their commercialization. Indian Council of Agricultural Research (ICAR) is an autonomous organization, and is the apex body for coordinating, guiding and managing research and education in agriculture in the entire country. With the aim of utilizing the vast research and development facilities and knowledge available with its institutions, ICAR has started a technology management and business incubation drive, intended for the Indian agricultural sector to promote agribusiness. This apex body has established a three-tier IP management system, which is presently giving a scope of demonstrated results by securing its research assets with different IP tools like patents, trademarks and designs; and commercializing its research outcomes. Six ICAR fisheries research institutes filed 84 patent applications, out of which 55 were filed during the last 5 years. Seven patents were conceded to 3 of these establishments, which fall under the IPC classifications A, B, C and E. Eight trademarks were additionally enlisted at the Indian Trademark Registry for diverse fish based products. To commercialize the fisheries research outcomes, including 142 technologies, 207 partnerships were developed by various institutes with 135 national and international organizations. IP protected technology commercialization is on its higher side with 21.12%, achieved within a short time span. These endeavors of technology management at ICAR, coupled with an effective technology protection and commercialization of the vast and diversified ICAR knowledge base, gave a renewed boost and a decent way for the Indian fisheries research and a new agribusiness paradigm.